Psychological compatibility and its relationship with self-esteem among a sample of secondary school students: A field study in some secondary schools in Laghoua - Chaki, Abdelhamid; Aoune, Ali (Journal of Human Sciences, 2022)
This study aimed to identify psychological compatibility and its relationship with self-esteem in secondary education pupils. The researchers relied on the descriptive and comparative correlative approach. The study included (120) students as the study community and selected (90) students in a simple random way. Dr. Attia Mahmoud here and the self-esteem of Rosenberg and after checking the validity and reliability of the two scales were adopted in our study.